The Development of KHI'S Business Model to Enhance Sustainable Competitive Advantage - Firdaus, Anton; Hamsal, Mohammad (The Indonesian Journal of Business Administration, 2013)
This research about how PT KHI make an improvement in Business model by offering EPC (Engineering, Procurement & Construction) services to costumer to gain a better profit margin. Research result suggests PT KHI to improve its Business Model in order to enhance sustainable competitive advantage. Many competitors have the same business model in industry. PT KHI should offer different business model to stay ahead and winning the competition. The research result indicate based on current condition at PT KHI, a new value proposition will increase companyâ€™s profitability to enhance sustainable competitive advantage. The author proposes PT KHI to innovate its business model through new proposed Business Model Canvas. Â Keywords; Business Strategy, Business Model, Business Model Canvas, Pipe Industry, Innovation